2014
DOI: 10.1074/jbc.m114.595207
|View full text |Cite
|
Sign up to set email alerts
|

Induction of the Unfolded Protein Response by Constitutive G-protein Signaling in Rod Photoreceptor Cells

Abstract: Background: Excessive light exposure and genetic mutations that act as "equivalent light" cause photoreceptor cell death. Results: Prolonged transducin signaling, but not channel closure, induces endoplasmic reticulum stress. Conclusion: Induction of UPR is a distinct cell death pathway caused by transducin signaling. Significance: Manipulation of UPR may prolong photoreceptor cell survival in transducin-induced retinal light damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 54 publications
1
26
0
Order By: Relevance
“…As expected, the GCAP2 signal was not observed in Gcap2 -/-or Gcaps -/-cones ( Fig. 1 bottom two panels), thereby confirming the specificity of the GCAP2 antibody (33). Together, these results clearly demonstrate that GCAP2 is expressed in mouse cones.…”
Section: Gcap2supporting
confidence: 71%
“…As expected, the GCAP2 signal was not observed in Gcap2 -/-or Gcaps -/-cones ( Fig. 1 bottom two panels), thereby confirming the specificity of the GCAP2 antibody (33). Together, these results clearly demonstrate that GCAP2 is expressed in mouse cones.…”
Section: Gcap2supporting
confidence: 71%
“…Moreover, the G90D mutation actually rescues the retinal degeneration induced by a mutation in the guanylate cyclase activating protein, GCAP-1, which leads to elevated levels of cGMP (Woodruff et al, 2007). Interestingly, a study of effects of phototransduction cascade mutants found evidence that constitutive G-protein activation due to inactivating mutations in rhodopsin kinase or arrestin, but not constitutive membrane hyperpolarization due to inactivation of the cGMP-gated cation channel that is the ultimate downstream target of the phototransduction cascade, led to activation of the Unfolded Protein Response (Wang and Chen, 2014). Thus, constitutive signaling may act on cell survival differently, depending on the step(s) of the cascade affected.…”
Section: Rod Dystrophiesmentioning
confidence: 99%
“…In addition, mutations of RPE65 that prevent formation of visual pigments are expected to lower [Ca 2+ ] due to the constitutive activity of free opsin proteins which continuously stimulate the phototransduction cascade (Woodruff et al, 2003). Other examples of mutations leading to uncontrolled phototransduction and photoreceptor cell death include the rod arrestin knockout (Chen et al, 1999b; Wang and Chen, 2014) and rhodopsin kinase knockout (Chen et al, 1999a) mouse models. Indeed, an “equivalent light” hypothesis has been put forward to explain how the dominantly active mutations in the phototransduction cascade lead to cell death (Fain, 2006; Fain and Lisman, 1993).…”
Section: Role Of Calcium In Photoreceptor Degenerationmentioning
confidence: 99%